HER2 loss in HER2‐positive gastric or gastroesophageal cancer after trastuzumab therapy: Implication for further clinical research. Issue 12 (16th September 2016) - Pietrantonio, F.; Caporale, M.; Morano, F.; Scartozzi, M.; Gloghini, A.; De Vita, F.; Giommoni, E.; Fornaro, L.; Aprile, G.; Melisi, D.; Berenato, R.; Mennitto, A.; et al.
Abstract : Mechanisms of acquired resistance to trastuzumab‐based treatment in gastric cancer are largely unknown. In this study, we analyzed 22 pairs of tumor samples taken at baseline and post‐progression in patients receiving chemotherapy and trastuzumab for advanced HER2‐positive [immunohistochemistry (IHC) 3+ or 2+ with in‐situ hybridization (ISH) amplification] gastric or gastroesophageal cancers. Strict clinical criteria for defining acquired trastuzumab resistance were adopted. Loss of HER2 positivity and loss of HER2 over‐expression were defined as post‐trastuzumab IHC score <3+ and absence of ISH amplification, and IHC "downscoring" from 2+/3+ to 0/1+, respectively. HER2 IHC was always performed, while ISH was missing in 3 post‐progression samples. Patients with initial HER2 IHC score 3+ and 2+ were 14 (64%) and 8 (36%), respectively. Loss of HER2 positivity and HER2 over‐expression was observed in 32 and 32% samples, respectively. The chance of HER2 loss was not associated with any of the baseline clinicopathological variables. The only exception was in patients with initial IHC score 2+ versus 3+, for both endpoints of HER2 positivity (80 vs . 14%; p = 0.008) and HER2 over‐expression (63 vs . 14%; p = 0.025). As already shown in breast cancer, loss of HER2 may be observed also in gastric cancers patients treated with trastuzumab‐based chemotherapy in the clinical practice. This phenomenon may be one of the biological reasons explaining the failure of anti‐HER2 second‐line strategies in initially HER2‐positive disease. Abstract : What's new? Patients with cancers positive for human epidermal growth factor receptor 2 (HER2) generally fail to respond to second‐line treatments, particularly when first‐line therapy included use of the HER2‐targeted agent trastuzumab. Post‐progression changes in HER2 expression, however, have not been studied extensively, and as a consequence, their therapeutic relevance is unclear. In this study, HER2 loss was associated with acquired resistance to trastuzumab in almost one‐third of patients with gastric or gastroesophageal cancers that initially were HER2‐positive. The findings suggest that after failure of trastuzumab, HER2 status should be reassessed prior to inclusion in clinical trials with targeted agents.